Experiencing Rupture: affective art and becoming-with slow emergencies - Virginia BARRATT; Jessie BOYLAN; Linda DEMENT (E-REA)
This paper provides an account of three artists’ exploration, together with a psychotherapist, of the ways in which they are engaging with the irreversible harm of the Capitalocene and its palpable manifestations within the body, as part of the world. Through polyvocality and poly-positionality, as well as being taken through the performance itself, this paper traces the development and presentation of the artwork Rupture, an interdisciplinary and collaborative work which brought together photo, video and sound artist Jessie Boylan, researcher, writer and performer Virginia Barratt, digital media artist Linda Dement and trauma-informed psychotherapist Jenna Tuke. Their collaboration and conversation, included in this account, inhabit how anxiety, as a warning system, is constantly triggered—not just at a bodily level, but also at a social and global ecological level—by daily messages of danger and catastrophe. Yet, by seeing anxiety’s capacity as a productive force, the authors ask : can we work together with the dead and dying, can we hold the pain of the earth/body and reconfigure the traumas beneath the surface to move us on from stasis ? Locating the work at the beginning of Australia’s worst-ever fire season, in late 2019, this paper provides the artists’ reflections on the process of making-with our catastrophic times.